2009
DOI: 10.1080/13691060802151887
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of private equity: what we know and what we would like to know

Abstract: Private equity and management buyouts have been the subject of considerable controversy. There have been recent calls for more systematic evidence on the impact of private equity and buyouts. Yet there is already an extensive body of scientific evidence stretching back over the past two decades that provides a platform for understanding the current context. This article summarises what we know about private equity from a comprehensive review of approximately 100 studies from around the world under the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 74 publications
0
42
0
1
Order By: Relevance
“…Specifically, several drawbacks have been associated with PE investments, particularly buy-out (BO), such as the excessive use of debt and the widespread practice of stripping the firm assets (e.g., Wright et al, 2009;Guo et al, 2011). As a consequence, there has been significant attention on the importance of regulation in this area (e.g., the Wall Street Journal reported that the SEC has recently launched a wide-ranging inquiry into the PE industry 3 ), and renewed emphasis has been placed on understanding whether and how PE investments create value for investing firms.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, several drawbacks have been associated with PE investments, particularly buy-out (BO), such as the excessive use of debt and the widespread practice of stripping the firm assets (e.g., Wright et al, 2009;Guo et al, 2011). As a consequence, there has been significant attention on the importance of regulation in this area (e.g., the Wall Street Journal reported that the SEC has recently launched a wide-ranging inquiry into the PE industry 3 ), and renewed emphasis has been placed on understanding whether and how PE investments create value for investing firms.…”
Section: Introductionmentioning
confidence: 99%
“…Holott a tudományosan ellenőrzött adatokat és korrekt módszertant alkalmazó "független" tanulmányok száma is eléri a százat, s ezek alapján kiegyensúlyozott álláspont szűrhető le a kockázatitőke-befektetések hatásáról (Wright-Gilligan-Amess [2009]). A tudományos szakirodalom már egy sor olyan témát megvizsgált, ami fényt derít a kockázati tőke hatását érintő alapvető kérdésekre.…”
Section: A Kockázatitőke-befektetéseket éRt Bírálatokunclassified
“…Both Davis et al (2011) and Wright et al (2009) correctly note that recent criticisms of private equity tend to focus on the later stage buy outs rather than the involvement of venture capitalists at the early stage of an organization's life-cycle. However, a significant proportion of existing empirical work has ignored this distinction and presents results for very large numbers of private equity transactions dominated by management buy outs.…”
Section: Introductionmentioning
confidence: 99%